Pengaruh New Normal Perception to Work Terhadap Organizational Citizenship Behavior - Deni Rusmawati Agustin; Kabul Wahyu Utomo; Meirani Harsasi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The Covid-19 pandemic that has hit the world since early 2020 has changed the way and style of working. In the new normal order, the Ministry of Finance is adapting to this situation by setting up a combination work scheme of Work from Home (WFH) or working from home and (Work from Office/WFO) or working in the office. In this research, the combination of WFH and WFO work is hereinafter referred to as the New Normal Perception to Work (NNPW) variable. The aim of this research is to find out whether New Normal Perception to Work (NNPW) is related to Organizational Citizenship Behavior (OCB). This research was conducted on employees of the Tax Service Office located in the city of Semarang with a population of 808 employees with a sample of 272 respondents. This research also uses the mediating variables of job satisfaction and Work Life Balance (WLB). Variable measurements were carried out using a Likert scale, and the response results were analyzed using Structural Equation Modeling (SEM) with the AMOS 22.0 application. The research results show that New Normal Perception to Work influences employee OCB behavior, WLB and job satisfaction. Work Life Balance is able to mediate the influence of the relationship between New Normal Perception to Work and OCB. Meanwhile, on the other hand, job satisfaction has no effect on OCB, and is unable to mediate the influence of the relationship between NNPW and OCB.